PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA STKIP WIDYA YUWANA - Rongan, Paskalis Ola; Wilhelmus, Ola Rongan (CREDENDUM: Jurnal Pendidikan Agama, 2020)
This study aims to determine the correlation between learning motivation and learning outcomes according to the perception of students at STKIP Widya Yuwana, Madiun. The research employed a quantitative approach. The total population of the study was 179 students, and a sample of 124 students was selected using the simple random sampling method. The primary variables measured in this study were learning motivation and learning achievement. The results revealed that all respondents (100%) acknowledged that learning motivation is closely related to academic achievement. Specifically, 57.3% of respondents perceived learning motivation as the driving force that encourages students to gain extensive knowledge and perform better in their studies. Additionally, 44.4% of respondents stated that students' academic achievement levels had a strong correlation with their level of learning motivation. Furthermore, 49.2% of respondents indicated that motivation plays a crucial role in providing encouragement and enthusiasm for students to achieve their desired academic success. In general, the findings support the study’s hypothesis that the higher a person's motivation to learn, the greater their opportunity to achieve higher academic performance.